Modeling and Animating Virtual Humans for Real-Time Applications - Hülsken, Frank; Eckes, Christian; Kuck, Roland; Unterberg, Jörg; Jrg, Sophie (International Journal of Virtual Reality, 2007)
We report on the workflow for the creation of realistic virtual anthropomorphic characters. 3D-models of human heads have been reconstructed from real people by following a structured light approach to 3D-reconstruction. We describe how these high-resolution models have been simplified and articulated with blend shape and mesh skinning techniques to ensure real-time animation. The full-body models have been created manually based on photographs. We present a system for capturing whole body motions, including the fingers, based on an optical motion capture system with 6 DOF rigid bodies and cybergloves. The motion capture data was processed in one system, mapped to a virtual character and visualized in real-time. We developed tools and methods for quick post processing. To demonstrate the viability of our system, we captured a library consisting of more than 90 gestures.